2020
DOI: 10.31224/osf.io/wx89s
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

X-Ray Image based COVID-19 Detection using Pre-trained Deep Learning Models

Abstract: Detecting COVID-19 early may help in devising an appropriate treatment plan and disease containment decisions. In this study, we demonstrate how pre-trained deep learning models can be adopted to perform COVID-19 detection using X-Ray images. The aim is to provide over-stressed medical professionals a second pair of eyes through intelligent image classification models. We highlight the challenges (including dataset size and quality) in utilising current publicly available COVID-19 datasets for developing usefu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 30 publications
1
70
0
Order By: Relevance
“…The ResNet50 plus SVM is statistically superior to other models with accuracy and the f1-score was 95.38%, 95.52% respectively. Horry et al [29] developed a system based on pre-trained model to detect COVID-19 from chest X-ray. They used Xception, VGG, Resnet, and Inception for the classification of COVID-19 patients.…”
Section: Related Workmentioning
confidence: 99%
“…The ResNet50 plus SVM is statistically superior to other models with accuracy and the f1-score was 95.38%, 95.52% respectively. Horry et al [29] developed a system based on pre-trained model to detect COVID-19 from chest X-ray. They used Xception, VGG, Resnet, and Inception for the classification of COVID-19 patients.…”
Section: Related Workmentioning
confidence: 99%
“…The VGG19 obtained high performance among others with an accuracy of 93.48%, specificity of 92.85%, and sensitivity of 98.75%. Horry et al [23] illustrated deep transfer learning based system and achieved the highest result for VGG19 with 83% recall and 83% precision for the diagnosis of COVID-19. Loey et al [24] proposed a deep transfer learning approach with three pre-trained CNN networks to diagnose coronavirus disease.…”
Section: Related Workmentioning
confidence: 99%
“…Apostolopoulos and Mpesiana (2020) used transfer learning CNN from MobileNetV2 and VGG19 to extract the features of COVID-19, bacterial pneumonia and normal cases and their approach showed an accuracy of 96.78%. Horry et al (2020) used four pre-trained ImageNet models for COVID-19 diagnosis and showed that VGG19 produces good results in prediction with a precision of 83%. Chowdhury et al (2020) used eight pre-trained neural networks to perform diagnosis between normal and COVID-19 and normal, pneumonia from COVID-19 i.e.…”
Section: Introductionmentioning
confidence: 99%